(untitled) (Educational Perspectives Magazine (REPED), 2023)
In spite of the important educational investments and transformations that are taking place in our society in order to improve the quality of education, the students’ educational achievement is still low and varíes according to social class. Families belonging to these groups face great difficulties to guarantee life necessary conditions for basic cognitive development and for an adequate primary socialization process. Under these conditions, the establishment of a real relationship between family and school is thoughl to be a priority if the quality of education has to be improved. This paper presents some reflections and research results about the relevance of family as a primary socialization agent; the importance of family and school relationship; the difficulties and obstacles to achieve such relationship and some strategies to make them to become closer.